2021
DOI: 10.11118/actaun.2021.044
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of a Composition of Selenium and Iodine Nanoparticles

Abstract: The aim of this study was to investigate antifungal properties of the composition of Se and I nanoparticles (NPs) against strains of phytopathogenic fungi Acremonium cucurbitacearum 502, Acremonium strictum 048 and Fusarium sp. 072. It has been found that the composition of Se and I NPs has antifungal properties against these strains. The highest antifungal activity was against strain A. cucurbitacearum 502, manifesting as the decrease in the number of colonies (by 60.00-86.67%) and the decrease of the diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…In studies with Candida glabrata it has been found that SeNPs attach and agglomerate on the surface of cells, cause loss of membrane’s smoothness, appearance of bulges and impairment of membrane’s integrity [ 124 ]. Vasylchenko and Derevianko [ 125 ] reported the strong antifungal activity of Selenium and iodine nanoparticles against Fusarium spp. Strong antifungal activity of green synthesized SeNPs was reported by Hashem et al, [ 126 ] Moreover, Lashin et al [ 127 ] confirmed SeNPs that biosynthesized from Ziziphus spina-christi exhibited antifungal activity against unicellular and multicellular fungi.…”
Section: Resultsmentioning
confidence: 99%
“…In studies with Candida glabrata it has been found that SeNPs attach and agglomerate on the surface of cells, cause loss of membrane’s smoothness, appearance of bulges and impairment of membrane’s integrity [ 124 ]. Vasylchenko and Derevianko [ 125 ] reported the strong antifungal activity of Selenium and iodine nanoparticles against Fusarium spp. Strong antifungal activity of green synthesized SeNPs was reported by Hashem et al, [ 126 ] Moreover, Lashin et al [ 127 ] confirmed SeNPs that biosynthesized from Ziziphus spina-christi exhibited antifungal activity against unicellular and multicellular fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Досліджено протигрибні властивості композиції наночастинок (НЧ) Se та I проти штамів фітопатогенних грибів Acremonium cucurbitacearum 502, Acremonium strictum 048 та Fusarium sp. 072 та рекомендовано для розробки заходів боротьби з фітопатогенними грибами [27].…”
Section: землеробство та рослинництво: теорія і практикаunclassified